2021
DOI: 10.3390/polym13020183
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Preparation and Anticorrosion Properties of EP/CeO2-GO Nanocomposite Coating

Abstract: Due to its special two-dimensional lamellar structure, graphene possesses an excellent shielding effect, hydrophobic characteristics and large specific surface area, which can effectively isolate the internal structure from the external corrosive media. However, lamellar graphene is easy to stack and agglomerate, which limits its anti-corrosion performance. In this paper, cerium oxide-graphene oxide (CeO2-GO) nanocomposites were prepared by a hydrothermal synthesis method. Field emission scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…When the carbon black was increased, ane increased corrosion current was observed due to the excess of carbon black inside the polymer. This behavior can be seen in other composite materials such as polyaniline/clinoptilolite nanocomposite, cerium oxidegraphene oxide, and multiwall carbon nanotubes-reinforced epoxy [30][31][32]. Electrochemical impedance spectroscopy is a technique that had been widely used to investigate the mechanisms of electrochemical applications [4].…”
Section: Resultsmentioning
confidence: 99%
“…When the carbon black was increased, ane increased corrosion current was observed due to the excess of carbon black inside the polymer. This behavior can be seen in other composite materials such as polyaniline/clinoptilolite nanocomposite, cerium oxidegraphene oxide, and multiwall carbon nanotubes-reinforced epoxy [30][31][32]. Electrochemical impedance spectroscopy is a technique that had been widely used to investigate the mechanisms of electrochemical applications [4].…”
Section: Resultsmentioning
confidence: 99%
“…The sample was ultrasonically cleaned in alcohol to remove the debris caused by the grinding and polishing procedure. CeO 2 -GO(4:1) nanocomposites were prepared by a hydrothermal synthesis method [ 21 ]. Then, 4 g epoxy was measured, and a certain amount of CeO 2 -GO(4:1) (0.5 wt% of the epoxy mass) was added to the epoxy after a 30 min ultrasonic dispersion process.…”
Section: Methodsmentioning
confidence: 99%
“…Cerium oxide (CeO 2 ) can be used as a nano-sheet layered material [ 19 , 20 ]. The study [ 21 ] has shown that when the mass ratio of CeO 2 to GO is 4:1, the anti-corrosion effect of epoxy(EP) coating with CeO 2 -GO nanocomposites is very significant. CeO 2 is evenly distributed on the GO surface, which improves the agglomeration of GO.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many efforts have been made to reduce its sheets aggregation by introduction of nanoparticles to the sheets so as to improve its dispersion in polymer. Liu et al 42 synthesized the cerium oxide‐GO composite material by hydrothermal method to greatly enhance the corrosion resistance of the composite coating to improve the accumulation and agglomeration of GO in epoxy resin.…”
Section: Introductionmentioning
confidence: 99%